DAMPAK KEBIJAKAN PENGURANGAN SUBSIDI PUPUK TERHADAP PENGGUNAAN PUPUK ALTERNATIF DAN PENDAPATAN USAHATANI MELON PUTIH (Cucumis melo ,L) : (Suatu Kasus Pada Petani Melon Merah di Kecamatan Patokbeusi, Kabupaten Subang, Provinsi Jawa Barat) - Handayana, Lucky Lukmansyah (Fakultas Pertanian Universitas Winaya Mukti, 2025)
LUCKY LUKMANSYAH, 2024. The Impact of the Fertilizer Subsidy Reduction Policy on the Use of Alternative Fertilizers and the Income of White Melon Farming (Cucumis melo L). (A Case on Red Melon Farmers in Patokbeusi District, Subang Regency, West Java Province). Under the guidance of Euis Dasipah and Nataliningsih. This study aims to determine the impact of the Fertilizer Subsidy Reduction Policy on the Use of Alternative Fertilizers and Income of White Melon Farming (Cucumis melo L). The technique of determining respondents was carried out by drawing a simple random sample of 45 units. The analysis technique used was t test analysis (t test paired). The results of the research obtained from the Fertilizer Subsidy Reduction Policy had an impact on the increase in the use of organic fertilizers as alternative fertilizers where previously used 2,205 kg/ha to 4,146/kg or an increase of 75.68%. The use of urea fertilizer decreased on average from 300 kg/ha to 200 kg/ha or 33.33% and NPK phonska fertilizer from 350 kg/ha to 250 kg/ha or 28.57%. The reduction in the use of urea and NPK phonska fertilizers does not have an impact on decreasing productivity and even tends to increase, due to the increase in organic fertilizers. The Fertilizer Subsidy Reduction Policy has an impact on increasing the production cost of white melon farming from Rp 35,247,955/ha to Rp 36,878,455/ha or an increase of 7.51% This is due to the increase in the use of organic fertilizers. The Fertilizer Subsidy Reduction Policy did not have an impact on decreasing the productivity of white melon farming, in fact there was an increase in productivity from 15,668 kg/ha to 17,111 kg/ha. This is due to the increasing use of organic fertilizers. Furthermore, the Fertilizer Subsidy Reduction Policy has had an impact on the decline in white melon farming income, even increasing from Rp 74,575,330/ha to Rp 82,575,470/ha.